O pai requerente da guarda unilateral dos filhos: avanços e obstáculos no âmbito do Judiciário - Freitas, Carlos David de (2022)
This research aims to understand the representations of paternity in the legal field, along with the practice of professionals who work in custody dispute cases in which the father obtained the unilateral custody of children. In this aspect, our question focused in analyzing what would be the understanding of paternity in the context of the judiciary, in the view of the parent’s claims for custody of the children. We have departed from the perception that despite the changes which have taken place in the paternity conception in today’s society, such as, a father’s more active participation in the child’s life, few advances and innovations have occurred in the legal field. We considered paternity custody is granted when, in fact, they reside with the father. Therefore, we aimed to polish the image of this one that emerges in the custody disputes through family speeches: Psychologists, Social Workers, and Law Operators e.g., Lawyers, Prosecutors and Judges. This is a descriptive documental research having our research field as a forum with two District Family Courts within a mediumsized city in the Midwest of São Paulo state. We have researched record books and the process automation system in which the parent is set as the requester from 2015 to 2019. Summing 251 processes, we have worked with 105 custody either granted to the parent or converted to shared guard, along with agreements during the process. These processes were, then, subjected to a lottery, having randomly been selected 10 out of them. We have concluded unilateral paternal custody was granted because, in fact, he was already the guardian of the children, officially regularizing the situation. It was shown that unlike the traditional model, the contemporary father is more affective and participatory in the children’s life, however the request for sole paternal custody occurred, in some cases, to rule out the actual situation and, in others, for reasons more associated with maternal behavior, than a questioning based on the demand for direct care by the parent. It was noticed that most of the time the father did not fully take care of the children, as he turned to his parents: grandparents, who effectively would take care of the children or the new partner. In the processes, we highlight the incapacity of maternal exercising and attributes of the father as more capable of exercising the care of children; such a situation emerging in the view of the fact that the mother was not consistent with the socially idealized model